I made it out of clay - Kander, Beth (Mira, 2024)
"Nothing's going well for Eve: she's single, turning forty, stressed at work, and anxious about a recent series of increasingly creepy incidents. Most devastatingly, her beloved father died last year, and her family still won't acknowledge their sorrow. With her younger sister's wedding rapidly approaching, Eve is on the verge of panic. She can't bear to attend the event alone. That's when she recalls a strange story her Yiddish grandmother once told her, about a protector forged of desperation--and Eve, to her own shock, manages to create a golem. At first, everything seems great. The golem is indeed protective--and also attractive. But when they head out to a rural summer camp for the family wedding, Eve's lighthearted rom-com fantasy swiftly mudslides into something much darker"--